Routine analysis of synchronized swimming at the 9th FINA World championships 2001 - Homma, Mi.; Ito, K.; Kubo, Y.; Takamatsu, J.; Ichikawa, H.; Homma, Ma. (Biomechanics and Medicine in Swimming IX, 2003)
INTRODUCTION The Scientific Committee of Japan Swimming Federation carried out a routine analysis project at the 9th FINA World Championships 2001. The purpose of this project was to analyze routine performances qualitatively and quantitatively from biomechanical aspect. METHODS Routine performances were videotaped from the catwalk, pool deck and underwater. The items of data analysis were pool, the horizontal traveling speed, total distance traveled, the height above the water surface and three dimensional motion analysis of the underwater movements. These data were analyzed for all routines in the Solo, Duet and Team Technical Routines. RESULTS The mean total distance the swimmer traveled throughout a routine in the Solo, Duet and Team were 50.38±4.22 m, 54.04±4.85 m, and 71.18±4.74 m respectively. The mean maximum body heights above the water surface were 1.05±0.10 m, 1.03±0.08 m, and 1.10±0.08 m respectively. In a comparison of the top 12 routines and others in each item, the total distance traveled of the Solo and Duet top 12 routines were higher than those of the other routines. However, there were no significant differences between the top 12 routines and others. In peak height, there was a significant difference between the top 12 routines and others (Fig.1). This indicated that the top 12 routines in the Solo and Duet had a greater height than the other routines. In mean height, there was also significant difference between the top 12 routines and others in the Duet. From these results, it was clear that height is an important factor for the performances.